Rat microsomes activating the anticancer drug ellipticine to species covalently binding to deoxyguanosine in DNA are a suitable model mimicking ellipticine bioactivation in humans - Stiborová, Marie; Stiborová-Rupertová, Martina; Borek-Dohalská, Lucie; Wiessler, Manfred; Frei, Eva (Chemical research in toxicology, 2003)
Ellipticine is a potent antineoplastic agent, whose mode of action is considered to be based mainly on DNA intercalation and/or inhibition of topoisomerase II. Recently, we found that ellipticine also forms covalent DNA adducts and that the formation of the major adduct is dependent on the activation of ellipticine by cytochrome P450 (P450). We examined rat, rabbit, and human hepatic microsomal samples for their ability to activate ellipticine. The extent of activation was determined by binding of 3H-labeled ellipticine to DNA and by analyzing DNA adducts by 32P-postlabeling. We demonstrate that cytochrome P450 of human hepatic microsomes activating ellipticine to species binding to DNA is analogous to that of rats, but not of rabbits. Most of the ellipticine activation in rat and human hepatic microsomes is attributed to P450 enzymes of the same subfamily, P450 3A1/2 and P450 3A4, respectively, while the orthologous enzyme in rabbit hepatic microsomes, P450 3A6, is much less efficient. With purified enzymes, the major role of P450 3A1 and 3A4 in ellipticine-DNA adduct formation was confirmed. We identified deoxyguanosine as the target for P450-mediated ellipticine binding to DNA using polydeoxyribonucleotides and deoxyguanosine 3'-monophosphate. The results strongly suggest that rats are more suitable models than rabbits mimicking the metabolic activation of ellipticine in humans.
Keywords: králíci; Rats; systém (enzymů) cytochromů P-450; zvířata; inhibitory cytochromu P450; izoenzymy; Isoenzymes; adukty DNA; Antineoplastic Agents; modely u zvířat; Humans; protinádorové látky; druhová specificita; Rabbits; jaterní mikrozomy; Species Specificity; lidé; DNA Adducts; inhibitory enzymů; Cytochrome P-450 Enzyme System; Deoxyguanosine; Cytochrome P-450 Enzyme Inhibitors; elipticiny; Animals; Phosphorus Radioisotopes; Ellipticines; radioizotopy fosforu; Enzyme Inhibitors; DNA; Models, Animal; krysa rodu Rattus; deoxyguanosin; Microsomes, Liver